3D Dentobox (Dental Explosion Box 3D) as education media for children caries prevention - Dewi, Siti Rusdiana Puspa; Utami AF, Deratih Putri; Octantia, Indah; Ifadah, Nurul (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2017)
Introduction: The most common dental and oral health problem in the world is dental caries. In Indonesia, as many as 89% of children under 12 years old suffered from dental and oral disease. Lack of dental knowledge and awareness can be overcome by conducting intensive dental and health education to the community. 3D Dentobox is a simple three-dimensional game designed to deliver dental and oral health messages, including dental hygiene, ways to overcome dental health problems and some dental games. 3D Dentobox is an educational media prevention of caries in children. Methods: The method used was Quasi experiment with the type of pretest and posttest control group design. The sample of this study was 30 children aged 9-12 years old. The research subjects filled out a questionnaire containing information on the level of knowledge, attitudes, and actions in caries prevention efforts followed by outreaching to the media and 3D props Dentobox and was given back the same questionnaire to be filled. Data were collected and evaluated using Guttman scale and was analyzed by paired T test. Results: The results showed that the average level of knowledge, changing attitudes, and actions before and after use 3D Dentobox increased significantly (p<0.05). Conclusion: 3D Dentobox can be used as a media of education to prevent dental caries in children.